2021
DOI: 10.3389/fphar.2021.759199
|View full text |Cite
|
Sign up to set email alerts
|

Control of Tissue Fibrosis by 5-Methoxytryptophan, an Innate Anti-Inflammatory Metabolite

Abstract: Tissue fibrosis causes debilitating human diseases such as liver cirrhosis, heart failure, chronic kidney disease and pulmonary insufficiency. It is a dynamic process orchestrated by specific subsets of monocyte-macrophages, fibroblasts, pericytes and hepatic stellate cells. Fibrosis is linked to tissue inflammation. Pro-inflammatory macrophages promote fibrosis by driving myofibroblast differentiation and macrophage myofibroblast transition. Myofibroblasts express α-smooth muscle cell actin (α-SMA) and secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…Cardiac fibrosis (CF) is characterized by cardiac fibroblasts hyperproliferation and extracellular matrix accumulation, which ultimately becomes an irreversible contributor to heart failure (HF) ( Travers et al., 2016 ; Wu, 2021 ). CF is an inevitable pathological process of HF.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac fibrosis (CF) is characterized by cardiac fibroblasts hyperproliferation and extracellular matrix accumulation, which ultimately becomes an irreversible contributor to heart failure (HF) ( Travers et al., 2016 ; Wu, 2021 ). CF is an inevitable pathological process of HF.…”
Section: Introductionmentioning
confidence: 99%
“…Through their interactions, they stimulate fibroblasts to differentiate into myofibroblasts, which release collagen and ECM proteins to cause myocardial fibrosis (MF). Thus, macrophage-mediated inflammatory tissue injury and MF are the primary pathophysiological processes that lead to LVR and HF after MI [9,23].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 5-MTP can inhibit the proliferation and migration of tumor cells by hampering the p38-MAPK/ NF-kB pathway, stenosis caused by the vascular injuryinduced proliferation of endothelial and smooth muscle cells, chronic kidney disease (CKD) progression as well as renal and liver fibrosis as seen in various studies on tumorigenesis [8], inflammation inhibition [9], peripheral artery disease [10], CKD [11], and liver fibrosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence indicates that the decrease in 5-MTP levels in ischemic heart tissue may be associated with the inhibition of tryptophan hydroxylase-1 by proinflammatory mediators [ 19 ]. Additionally, 5-MTP has been shown to effectively prevent injury-induced liver, kidney, heart, and lungs, by inhibiting macrophage activation and preventing fibroblast differentiation [ 20 ]. Our study confirmed that 5-MTP significantly inhibited inflammation, decreased LA fibrosis, and reduced AF vulnerability in rats treated with ibrutinib-treated.…”
Section: Discussionmentioning
confidence: 99%